Historical DNA as a tool to genetically characterize the Mediterranean sand tiger shark (Carcharias taurus, Lamniformes: Odontaspididae): A species probably disappeared from this basin. Issue 5 (6th February 2020) - Fioravanti, Tatiana; Bargnesi, Filippo; Splendiani, Andrea; Giovannotti, Massimo; Renzi, Francesca; Caputo Barucchi, Vincenzo
Abstract: The sand tiger shark ( Carcharias taurus ) is a coastal species distributed in temperate and sub‐tropical waters, classified as 'Vulnerable' at global level and 'Critically endangered' in eastern Australia, south‐western Atlantic Ocean, and Mediterranean Sea. Six populations (north‐western Atlantic, Brazil, South Africa, Japan, eastern Australia, and western Australia) with low genetic diversity and limited gene flow were identified worldwide, but genetic information for many other geographic areas are still missing. Specifically, this species is listed in several reports as part of the Mediterranean fauna, even if there has been a lack of catches and sightings in recent years in this basin. To clarify the origin of C. taurus individuals caught in the past in the Mediterranean Sea, historical samples were genetically analysed. Nine samples with certain Mediterranean origin were collected from different European museums. DNA was extracted and ~600 bp of the mitochondrial DNA control region were amplified using eight overlapping species‐specific primer pairs. Sequences obtained were aligned with all the haplotypes globally known so far. Genetic analysis revealed the misidentification of one museum specimen. Among the remaining Mediterranean historical samples, three different haplotypes were recovered. Two of them previously observed only in South Africa and one described in both South African and Brazilian populations. Results suggest a genetic relationship between Mediterranean sand tiger sharks and those from the western Indian Ocean. According to previous studies, we hypothesized that, during the Pleistocene, the cold Benguela upwelling barrier was temporarily reduced allowing the passage of C. taurus individuals from the Indian to Atlantic Ocean. After the restoration of this phylogeographic barrier some individuals were trapped in the Atlantic Ocean and probably migrated northward colonizing the western African coasts and the Mediterranean Sea.